ANALYSIS OF SHAPE-PHASE VARIATIONS AND FLUCTUATIONS IN HEATED FAST ROTATING EVEN-EVEN TRANSITIONAL NUCLEI WITH N∼ 84 - SANTHANA PRIYA R; SELVAM V (The Bioscan, 2023)
Employing the Landau theory of phase transitions, which has been extended to encompass higher orders of deformation, we examine the shape evolution of Neodymium isotopes, specifically 144Nd and 146Nd, in relation to temperature and spin. The expansion of the free energy up to sixth power in β is used in these calculations. The spin dependence is introduced by additional constants which are obtained by fitting with the temperature-dependent moment of inertia. Thermal fluctuations are included in the usual way. Pairing is included in the study in an indirect way by solving the coupled equations. We show that in the presence of thermal fluctuations, the average shapes differ from the most probable shapes.